OPERATIONAL RISK MANAGEMENT IN FINNISH INSURANCE COMPANIES (CASE: COMPANY X) - Jalasto, Jussi (My University, 2016)
Operational risk management is one of the broadest functions of any financial institution and one of the hardest to control. It is also a rather new risk category; companies around the world are paying more and more attention to operational risks. Financial institutions and researchers have realized that it is essential to try to identify all risks, not only market, credit and strategic, but also operational risks. The aim of this study is to investigate the existence of operational risks in Finnish insurance companies, especially Company X, and clarify the key operational risks. In terms of operational risk and operational risk management Finnish insurance companies are on the borders of transition. It is important to analyze the current stage of operational risk management so that further development could take place in the future. The data in this qualitative research has been collected from interviews with operational risk managers working at insurance companies in Finland and from the employees of Company X. Operational risk managers from Finnish insurance companies offer a broad and professional perspective to the questions while employees from Company X bring a more detailed and pragmatic approach to the answers. Interviewees responded to a questionnaire that was sent to them before face-to-face interviews. The results show that Finnish insurance companies are very aware of operational risks, but the tools used are still relatively simple. Systems-related risks, human risks, technological development and regulations are the four main operational risks that Finnish insurance companies face today. There is one clear similarity between the tools and methods used by insurance companies in Finland and it is also the tool used to prioritize resources for operational risk management. The results provide evidence that operational risk management in Finnish insurance companies needs further and more specific research so that companies could improve their own operational risk management.
Keywords: Operational risk; insurance company; regulations; system; fi=Laskentatoimi ja rahoitus|en=Accounting and Finance|; fi=Master's Degree Programme in Finance|